Differential properties of cytomegalovirus pUL97 kinase isoforms affect viral replication and maribavir susceptibility - Webel, Rike; Hakki, Morgan; Prichard, Mark N.; Rawlinson, William D.; Marschall, Manfred; Chou, Sunwen (Journal of Virology, 2014)
The human cytomegalovirus (HCMV)-encoded kinase pUL97 is required for efficient viral replication. Previous studies described two isoforms of pUL97, the full-length isoform (M1) and a smaller isoform likely resulting from translation initiation at codon 74 (M74). Here, we report the detection of a third pUL97 isoform during viral infection resulting from translation initiation at codon 157 (isoform M157). The consistent expression of isoform M157 as a minor component of pUL97 during infection with clinical and laboratory-adapted HCMV strains was suppressed when codon 157 was mutagenized. Viral mutants expressing specific isoforms were generated to compare their growth and drug susceptibility phenotypes, as well as pUL97 intracellular localization patterns and kinase activities. The exclusive expression of isoform M157 resulted in substantially reduced viral growth and resistance to the pUL97 inhibitor maribavir while retaining susceptibility to ganciclovir. Confocal imaging demonstrated reduced nuclear import of amino-terminal deletion isoforms compared to isoform M1. Isoform M157 showed reduced efficiency of various substrate protein interactions and autophosphorylation, whereas Rb phosphorylation was preserved. These results reveal differential properties of pUL97 isoforms that affect viral replication, with implications for the antiviral efficacy of maribavir.The HCMV UL97 kinase performs important functions in viral replication that are targeted by the antiviral drug maribavir. Here, we describe a naturally occurring short isoform of the kinase that when expressed by itself in a recombinant virus results in altered intracellular localization, impaired growth, and high-level resistance to maribavir compared to those of the predominant full-length counterpart. This is another factor to consider in explaining why maribavir appears to have variable antiviral activity in cell culture and in vivo.
EVALuna2:8230